MAKNA PROPERTI TARI BAKONCONG DALAM RITUAL ADAT SUKU DAYAK BADAMEA DI DESA SANATAP KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS - Melina, Trivena; Fretisari, Imma; Ismunandar, Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrakThis study aims to determine the meaning of the dance property required to disclose when using hand-property and set property. Hand-property comprises Handkerchief and Salapa which means as intermediaries for prayers to Jubata, and Set property used in the form of offerings has a unifying meaning of prayer delivered to Jubata to grant. This research is a descriptive study on Bakoncong dance in Sanatap Village, Sajingan Besar District, Sambas Regency. We carried this qualitative research out using a semiotic approach relating to the system of signs and symbols in human life. The data retrieved in this study results from interviews with informants Konen Felsia, Hendrikus Alek Kenek, and Domianus Jidat. Data collection techniques used were the observation, interviews, and documentation, while the data collection tools used were researchers as the main instruments, observation sheets, interview guidelines, and documentation tools. Data validation was by extended observation techniques, technique triangulation, and source triangulation. Keywords: Meaning, dance property, Bakoncong dance, Dayak tribe Badamea